Genetic diversity of Chinese common bean (Phaeolus vulgaris L.) landraces assessed with simple sequence repeat markers - Zhang, X.; Blair, Matthew W.; Wang, S. (Springer, 2008)
Common beans were introduced from the Americas to China over 400 years ago and presently constitute an important export crop in many areas of the country. Evaluation of the genetic diversity present in Chinese accessions of common beans is essential for conservation, management and utilization of these genetic resources. The objective of this research was to evaluate a collection of 229 Chinese landraces with 30 microsatellite markers to evaluate the genetic variability, genepool identity and relationships within and between the groups identified among the genotypes. A total of 166 alleles were detected with an average of 5.5 alleles per locus for all microsatellites. The landraces were clustered into two genepools with two subgroups each. The level of diversity for Chinese landraces of Andean origin was higher than for the Chinese landraces of Mesoamerican origin due to the presence of more infrequent alleles in this first group. The range of marker prevalence indices was from 0.288 to 0.676 within the Andean group and from 0.426 to 0.754 within the Mesoamerican group. Two subgroups were identified in each genepool group with one of the Mesoamerican subgroups arising from introgression. Gene flow (N m ) was 0.86 or below between subgroups from different gene pools and 2.6 or above between subgroups within the genepools. We discuss the existence of a secondary center of diversity for common beans in China and the importance of inter genepool introgression.